Implementasi Supervisi Kepala Sekolah Sebagai Penunjang Kinerja Guru di RA Plus Al-Mubarokah Boro - Ahmad Mushlih; Amalia Novianti (incrementapedia, 2022)
This study was to determine the application of educational supervision by the principal in improving teacher performance at the RA Plus Al-Mubarokah Boro institution.  Supervision aims to improve the quality and performance of educators, so that the role of supervision in the education management process has an important role.  It is hoped that this research can be believed to be a useful thought in the future, especially those related to supervision in ECE institutions in order to improve teacher performance.  This study uses a qualitative approach while the method used is descriptive qualitative.  Data was collected by using interview, observation and documentation studies.  The data obtained were then grouped, selected based on quality and analyzed descriptively, the results concluded to answer the existing problems.  The subjects of this study were the principal and teachers.  The results showed that the supervision activities carried out by the principal could support the teacher's performance.